Applications and Immunological Effects of Quantum Dots on Respiratory System - Ren, Laibin; Wang, Lingwei; Rehberg, Markus; Stoeger, Tobias; Zhang, Jianglin; Chen, Shanze (Frontiers in Immunology, 2022)
Quantum dots (QDs), one kind of nanoscale semiconductor crystals with specific electronic and optical properties, offering near-infrared mission and chemically active surfaces. Increasing interest existed in developing theranostics platforms for bioapplications such as imaging, drug delivery and therapy. Here we summarized QDs’ biomedical applications, toxicity and immunological effects on the respiratory system. Bioapplications of QDs in lung include biomedical imaging, drug delivery, bio-sensing or diagnosis and therapy. As generically for nanoparticles, their toxic effects are related to the generation of oxidative stresses, with subsequent DNA damage and lung cells decreasing viability in vitro and in vivo, with the addition of material specific release of toxic metal ions upon uptake. Lastly, pulmonary immunological effects of QDs mainly involve proinflammatory cytokines release and recruiting innate or adaptive leukocytes cells.